Post-Crisis Bank Behavior : Lessons From Mercosur - Sanya, Sarah (IMF Working Papers; Working Paper ;, 2010)
Did the occurrence of systemic banking crises in the 1990s and 2000s significantly alter the behavior of banks in the Mercosur? The objective of this paper is to answer this question by analyzing changes in bank behavior after crises in the Mercosur region. To our knowledge, this is the first paper to apply the convergence methodology-which is common in the growth literature-to post-crisis bank behavior. Using a panel dataset of commercial banks during the period 1990-2006, we analyze the impact of crises on four sets of financial indicators of bank behavior-profitability, maturity preference, credit supply, and risk. The paper finds that most indicators of bank behavior, such as profitability, in fact revert to previous or more normal levels. However, a key finding of the paper is that private sector intermediation is significantly reduced for prolonged periods of time and that high levels excess liquidity persist well after the crisis.